Sociotechnical Change and Institutional Adjustment in Paddy Rice Farming During Post Green Revolution in Indonesia - Awaluddin Yunus; Darmawan Salman; Eymal B. Demmallino; Ni Made Viantika (Hasanuddin University, 2016)
The development of rice field agriculture in Indonesia has entered the post green revolution phase. The sociotechnical changes occurred during the green revolution, the economic gap among farmers also ensued amid the increase in production while the social sustainability was maintained. The research purpose is to analyze the institutional adjustment conducted by the farmer society in facing the problems caused by green revolution in order to maintain the social sustainability. For the purpose mentioned above, the case study was carried out in a village in a center of green revolution. The result of the research shows that: (1) The sociotechnical changes had been taking place during the pre-green revolution era, green revolution, and post-green revolution in the form of land management, seeds procurement, planting and managing the crops, and harvest and post-harvest. The sociotechnical changes encouraged the increase in agricultural production in which created the gap between the affluent and the underprivileged in a village and had the potential to disturb the social sustainability of rice field agribusiness. (2) The institutional adjustment occurred in the sociotechnical changes in the forms of land ownership dynamics, employment dynamic and village’s new occupation dynamic. This institutional adjustment has the function to dampen the tension on the marginalized individual actor caused by the post green revolution new social structure. (3) The social sustainability in the rice field agriculture could be maintained because the social tension caused by the post green revolution social technical changes could be dampened by the institutional adjustment. The institutional adjustment by the village community contributed into the social sustainability of the rice field agribusiness.